Feasibility of Identifying Household Contacts of Rifampin-and Multidrug-resistant Tuberculosis Cases at High Risk of Progression to Tuberculosis Disease. (28th March 2019) - Gupta, Amita; Swindells, Susan; Kim, Soyeon; Hughes, Michael D; Naini, Linda; Wu, Xingye; Dawson, Rodney; Mave, Vidya; Sanchez, Jorge; Mendoza, Alberto; Gonzales, Pedro; Kumarasamy, Nagalingeswaran; et al.
Abstract: Background: We assessed multidrug-resistant tuberculosis (MDR-TB) cases and their household contacts (HHCs) to inform the development of an interventional clinical trial. Methods: We conducted a cross-sectional study of adult MDR-TB cases and their HHCs in 8 countries with high TB burdens. HHCs underwent symptom screenings, chest radiographies, sputum TB bacteriologies, TB infection (TBI) testing (tuberculin skin test [TST] and interferon gamma release assay [IGRA]), and human immunodeficiency virus (HIV) testing. Results: From October 2015 to April 2016, 1016 HHCs from 284 MDR-TB cases were enrolled. At diagnosis, 69% of MDR-TB cases were positive for acid-fast bacilli sputum smears and 43% had cavitary disease; at study entry, 35% remained smear positive after a median MDR-TB treatment duration of 8.8 weeks. There were 9 HHCs that were diagnosed with TB prior to entry and excluded. Of the remaining 1007 HHCs, 41% were male and the median age was 25 years. There were 121 (12%) HHCs that had new cases of TB identified: 17 (2%) were confirmed, 33 (3%) probable, and 71 (7%) possible TB cases. The TBI prevalence (defined as either TST or IGRA positivity) was 72% and varied by age, test used, and country. Of 1007 HHCs, 775 (77%) were considered high-risk per these mutually exclusive groups: 102 (10%) were aged <5 years; 63 (6%) were aged ≥5 and were infected with HIV; and 610 (61%) were aged ≥5 years, were negative for HIV or had an unknown HIV status, and were TBI positive. Only 21 (2%) HHCs were on preventive therapy. Conclusions: The majority of HHCs in these high-burden countries were at high risk of TB disease and infection, yet few were receiving routine preventive therapy. Trials of novel, preventive therapies are urgently needed to inform treatment policy and practice. Abstract : In a cross-sectional study of multidrug-resistant tuberculosis cases and household contacts in 8 countries, of 1007 contacts screened for tuberculosis, 121 (12%) had new TB identified. Tuberculosis infection prevalence was 72%. Trials of novel preventive therapies are urgently needed.